THE FLUCTUATION OF STUDENTS’ LEARNING MOTIVATION: A CASE STUDY OF LEARNING NAHWU IN ARABIC LANGUAGE AND LITERATURE DEPARTMENT OF UIN MAULANA MALIK IBRAHIM MALANG - Basid, Abdul; Habibi, Nashrul; Rosyidah, Ainun (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The aims of this study are to describe the types of the fluctuation of students’ learning motivation, their causes, and their impacts in learning Nahwu in Arabic Language and Literature Department of UIN Maulana Malik Ibrahim Malang. This study is a qualitative study. This study is also a case study. The subject of this study is students of Arabic Language and Literature Department of UIN Maulana Malik Ibrahim in 2017 academic year. The techniques of data collection used is questionnaire. The techniques of data validation used are increasing the preseverance, applying trianggulation, and discussing with the experts. The technique of data analysis used is Miles and Huberman model. The technique consists of three phases: reducting data, displaying data, and drawing clonclusion. The results of this study are: 1) the types of the fluctuation of students’ learning motivation are the flux and the reflux of students’ learning motivation, the detailed explanation as follow: the types of the flux of students’ motivation are students become increasingly diligent as active learning in the classroom, before going into the classroom and repeating material that had been given; The types of the reflux of students’ motivation are students are being lazy as silent, being passive in class and playing something more interest for them; 2) the causes of the fluctuation of students’ motivation are appearing a huge desire to master the Arabic language from various aspects so as to be able to read the book, making poetry, speaking fluently and so on; and the cause of the reflux of students’ motivation is a very complicated material; and 3) the impacts of the fluctuation of students’ motivation are students quickly understand the materials and the value of the study is higher; and the impact of the reflux of students’ motivation is students become increasingly lazy and the value of the study is lower.